Solvent Extraction of Palladium with 8-Mercarptoqinoline - Arvind T. Rane, (Late); R. Nepali, Deepawati (Asian Journal of Chemistry, 2010)
The solvent extraction equilibrium and kinetics of palladium extraction by 8-mercaptoquinoline have been studied radiometrically in chloroform, at ambient temperature (28ºC), and ionic strength 0.1M. The extractable complex is a diadduct, i.e. two molecules of the reagent are coordinated to the palladium(II) chelate. The adduct formation constant in chloroform and the overall formation constant of the palladium chelate in aqueous solution have been determined. The palladium complex is extractable from pH 1 to 9 uniformly. The rate of palladium(II) extraction by 8-mercaptoqunoline is first order with respect to [8-mercaptoquinoline] and the extraction rate constants were evaluated. Procedure was developed for the radiochemical separation of high specific active 100Pd from cyclotron irradiated ruthenium.